Gaseous emissions during concurrent combustion of biomass and non-recyclable municipal solid waste - Laryea-Goldsmith, Rene; Oakey, John E.; Simms, Nigel J. (Cranfield University, 2011)
Background: Biomass and municipal solid waste offer sustainable sources of energy; for example to meet heat and electricity demand in the form of combined cooling, heat and power. Combustion of biomass has a lesser impact than solid fossil fuels (e. g. coal) upon gas pollutant emissions, whilst energy recovery from municipal solid waste is a beneficial component of an integrated, sustainable waste management programme. Concurrent combustion of these fuels using a fluidised bed combustor may be a successful method of overcoming some of the disadvantages of biomass (high fuel supply and distribution costs, combustion characteristics) and characteristics of municipal solid waste (heterogeneous content, conflict with materials recycling). It should be considered that combustion of municipal solid waste may be a financially attractive disposal route if a 'gate fee' value exists for accepting waste for combustion, which will reduce the net cost of utilising relatively more expensive biomass fuels. Results: Emissions of nitrogen monoxide and sulphur dioxide for combustion of biomass are suppressed after substitution of biomass for municipal solid waste materials as the input fuel mixture. Interactions between these and other pollutants such as hydrogen chloride, nitrous oxide and carbon monoxide indicate complex, competing reactions occur between intermediates of these compounds to determine final resultant emissions. Conclusions: Fluidised bed concurrent combustion is an appropriate technique to exploit biomass and municipal solid waste resources, without the use of fossil fuels. The addition of municipal solid waste to biomass combustion has the effect of reducing emissions of some gaseous pollutants.
Keywords: coal